2016
DOI: 10.1186/s12890-016-0341-y
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity markers and lung function in smokers: a cross-sectional study in a Mediterranean population

Abstract: BackgroundThe aim of this study was to assess the association of key adiposity markers with lung function in smokers without respiratory disease in a Mediterranean population.MethodsWe performed a cross-sectional study with baseline data from a representative sample of the ESPITAP study in Spain. Participants were 738 smokers (52.3% men) without respiratory disease, aged 35 to 70, selected from 12 primary health care centres. We assessed weight, height, body mass index (BMI), waist circumference (WC) and waist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…As mentioned previously, measures such as WC are more accessible, but cannot differentiate abdominal compartments, which is the main objective of this study. WC and PF results, as other body measures in this same population, can be found in previous publication [ 19 ]; the present findings are in accordance with other previous studies that had investigated central obesity by different measure methods and research settings [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…As mentioned previously, measures such as WC are more accessible, but cannot differentiate abdominal compartments, which is the main objective of this study. WC and PF results, as other body measures in this same population, can be found in previous publication [ 19 ]; the present findings are in accordance with other previous studies that had investigated central obesity by different measure methods and research settings [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results of the previous studies regarding the association between BMI and FEV 1 or FVC were inconclusive. 13,[28][29][30][31][32] A cross-sectional study based on the British community did not find a linear association between BMI and FEV 1 or FVC among 2633 adults, which was in accordance with our results. 30 However, a cross-sectional study conducted in Mediterranean smokers found that BMI was inversely associated with lung function.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies showed that gender modified the effect of obesity on lung function. 13,42 In our analyses, the inverse Notes: † Models were adjusted for gender (male/female), age (continuous), height (continuous), weight (continuous), city (Wuhan/Zhuhai), occupational hazard exposure (yes/no), drug status (yes/no), smoking status (smokers/nonsmokers), drinking status (drinkers/nondrinkers), regular physical activity (yes/no), cooking meals at home (yes/ no), and family income (≥40,000/<40,000 RMB/year). ‡ Models were adjusted for † models without height (continuous).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This distinction is important because central obesity—which can be assessed by waist circumference (WC)—likely has a direct mechanical effect on pulmonary function. Indeed, central obesity is a marker of visceral adipose tissue, and is a critical determinant of a restrictive (rather than obstructive) spirometric pattern . On the other hand, general obesity is typically associated with a chronic state of low‐grade inflammation, and this likely contributes to increased airway wall thickness, increased baseline airway tone and increased vascular congestion of the airway wall …”
Section: Introductionmentioning
confidence: 99%